Comparison of slot tolerance with manufacturing measurements of different stainless steel self-ligating brackets - Aftan , Noor L.; Al-Groosh , Dheaa H; Albarkheel , Abdullah (Journal of Baghdad College of Dentistry, 2024)
Background: Bracket slot dimensions is of great interest to orthodontists as it plays a major role in torque expression by affecting the wire/ slot play. This study was designed to measure slot tolerance (dimensions) and convergence angles of different stainless steel self-ligating brackets and to compare between the chosen brands. Materials and methods: Eighty upper first premolar brackets of four different brands Damon Q (Ormco corporation, Brea, California, USA), DTC (Medical apparatus Cor., Hangzhou, China), IOS (Pactive self-ligating bracket, IOS, Stafford, USA), Lotus Plus interactive bracket (Orthotechnology Inc., southern Ct, West Columbia, USA) of stainless steel self-ligating brackets with claimed slot dimensions of 0.559 mm (0.022") in height, 0.711mm (0.028") in depth and with zero taper angle were used (twenty brackets of each brand). Brackets were mounted in a purposely planned way to ensure the parallelism of the slot’s walls and assessed using an inverted fluorescent optic microscope. The slot dimensions measurements were done using an AutoCAD software version 2020. One sample t-test was done to compare between brands and nominal values and One-way ANOVA with Tukey tests were done to compare between brands. Results: Actual slot dimensions were different significantly from the manufacturing measurements; the DTC bracket had the largest slot height and depth compared with manufacturing values (0.571mm, 0.741mm respectively), while the Lotus Plus bracket had significantly the lowest slot height and depth (0.549mm, 0.504mm respectively). Furthermore, DTC and IOS brackets have convergent slot walls, whereas Lotus Plus and Damon Q brackets exhibited divergent slot walls where Damon Q showed significantly the highest mean value (2.81◦). Conclusion: Apart from IOS brackets, the slot tolerances of the other brands did not comply with the manufacturer’s specifications. Moreover, DTC and IOS showed a convergence slot angle, while Damon Q and Lotus Plus brackets showed a divergent one.